Factors that influence employee performance in Johor Port Authority (JPA) / Ain Shamiera Norhadi - Norhadi, Ain Shamiera (2018)
Employee performance is indeed a very significant matter that need to be considered in an organization. The performance of employee within organization could directly affect the success of any business or organization performance. Organization that has properly managing its employee performance can help to increase their profits or sales. It is crucial in this globalization era to have competitive, motivated and proactive employee so that organization could compete and strengthen their position in market or industry. Existing recorded indicated that the present employee performance in the organization is still low and below expectation. Thus, this research addresses the determinants of employee performance in Johor port Authority. This study is conducted to determine the relationship between independent variable which are motivation, discipline and leadership style with employee performance. This study has been conducted using quantitative study while the research instrument that being used is self-administered questionnaire. Besides that, non-probability sampling (convenience) has been used as the sampling method and the total number of respondents is 108 person. In addition, this study has been used Statistical Package for the Social Science (SPSS) Version 22.0 to analyze the data analysis and findings. Finally, it is found that motivation, discipline and leadership style are significantly influence employee performance meanwhile, motivation is the most influential factor towards employee performance.